Community structure and diversity of macrobenthos in Jiaozhou Bay. (October 2021) - Wang, Zongxing; Wang, Hongping; Fan, Shiliang; Xin, Ming; Sun, Xia
Abstract: To understand the current community structure and diversity of macrobenthos in Jiaozhou Bay, a survey was conducted at eight sampling stations in April, July, and October 2018, as well as January 2019. Eighty-two macrobenthos species were collected, including 30 of Annelida, 21 of Mollusca, 20 of Crustacea, 8 of Echinodermata, and 3 classified as "Others". Ruditapes philippinarum was a common dominant species in summer, autumn, and winter. The annual average abundance and biomass were 280 ind./m 2 and 446.45 g/m 2, respectively. Shannon-Wiener diversity varied from 0.09 to 2.45 with an average value of 1.14. Margalef richness was 0.17–2.32 with an average value of 0.89. Pielou evenness was 0.14–1.00 with an average value of 0.71. The seasonal variation patterns of all tested indices were largely the same, with the highest in spring, next highest in winter, and lower in summer and autumn. The diversity at different survey stations varies greatly. Highlights: Jiaozhou Bay is heavily affected by anthropogenic activities. Seasonal changes of macrobenthic community structure and diversity in Jiaozhou Bay was studied. A total 82 species belonging to 5 phyla, 10 classes, and 58 families of macrobenthos were identified. Annelida had the highest species number, Molluscs had the highest abundance and biomass.